Acidic and alkaline gas sensitive and self-healing chitosan aerogel based on electrostatic interaction. (15th November 2021) - Zhao, Jin; Xi, Xiaotian; Ouyang, Hongyan; Yang, Jiyu; Wang, Yi; Yi, Longfei; Song, Dayu; Song, Yongjiao; Zhao, Lijuan
Abstract: Gas pollution is a serious problem. More attention has been paid to the detection and monitoring of toxic and harmful gases, and it is urgently needed for a sensor that could simultaneously identify and distinguish between acid and base gases. Based on the electrostatic interaction resulting from amidogen of chitosan (CS) and carboxylic groups of itaconic acid (IA), we successfully prepared a series of biomass aerogels (CS-IA aerogels) that could respond to acidic and alkaline gases with different concentrations. The acidic and alkaline gases could be easily detected and distinguished by changing the content of IA in CS-IA aerogels. Moreover, the electrostatic interactions could also endowed CS-IA aerogels with self-healing ability in the breaks at room temperature. After self-healing, CS-IA aerogels still sensitively answered to acidic and alkaline gases. CS-IA aerogels with sensitivity to acid-base gas and self-healing performance has been suggested to be promising candidates as application of multi-functional aerogels. Graphical abstract: Unlabelled Image Highlights: Self-healing aerogel Acid-base sensitivity property Electrostatic interaction